The Analysis of Research of Computer Subjects of Pupils-Members of Small Academy of Sciences of Ukraine in Khmelnitskiy Region - Sukhovirskyi, Oleh (Pedagogical Discourse, 2011)
The results of the researches presented on II stage of All Ukraine competition-protection of research of pupils-members of Small Academy of Sciences of Ukraine in Khmelnitskiy region analysed in the article. The most widespread mistakes in research are described, recommendations as for their avoidance are offered. The conclusion about the on tendencies of development of school computer science is done.